2001
DOI: 10.1021/om010087c
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Carbon−Carbon Bond Activation ofsec-Alcohols by a Rhodium(I) Complex

Abstract: Various unstrained sec-alcohols, including cycloalkanols, reacted with alkenes under a catalytic system of Rh(I) complex, 2-amino-3-picoline, and K2CO3 to give the alkyl-group-exchanged ketones through transfer hydrogenation and consecutive carbon−carbon bond activation. The presence of base is essential to enhance the rate of the oxidation step, and alkene acts as a hydrogen acceptor and a substrate of the carbon−carbon coupling reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 50 publications
0
20
0
2
Order By: Relevance
“…This is proposed to be aided by the picoline catalyst 5,w hich can form imine 6 with the ketone substrate (Scheme 4B). [32] 2.3. To favor the formation of the products,anexcess of alkene is typically employed, but the authors also suggest that the styrene by-product can polymerize under the reaction conditions, [28] thereby providing af urther driving force.O verall, this reaction is au seful complement to traditional hydroacylation processes, [29] wherein an alkene inserts directly into an aldehyde,s ince there are cases where the use of the bare aldehyde is unfavorable.F or example,a cetaldehyde can be ac hallenging substrate to work with.…”
Section: Rcho Transfermentioning
confidence: 99%
“…This is proposed to be aided by the picoline catalyst 5,w hich can form imine 6 with the ketone substrate (Scheme 4B). [32] 2.3. To favor the formation of the products,anexcess of alkene is typically employed, but the authors also suggest that the styrene by-product can polymerize under the reaction conditions, [28] thereby providing af urther driving force.O verall, this reaction is au seful complement to traditional hydroacylation processes, [29] wherein an alkene inserts directly into an aldehyde,s ince there are cases where the use of the bare aldehyde is unfavorable.F or example,a cetaldehyde can be ac hallenging substrate to work with.…”
Section: Rcho Transfermentioning
confidence: 99%
“…In Hinblick auf den Mechanismus wird angenommen, dass der Picolinkatalysator 5 mit dem Ketonsubstrat ein Imin 6 bildet (Schema 4B). [32] Um die Bildung des Produktes zu begünstigen, wird normalerweise das Alken im Überschuss eingesetzt.…”
Section: Rcho-transferunclassified
“…In 1999, the Jun group reported as eminal example of CÀC bond activation, and one of the earliest examples of shuttle catalysis, that enables the hydroacylation of alkenes. [8] The authors found that through the co-operativec atalysis of ar hodium catalyst and 2-aminopicoline 1 the hydroacylation of alkenes could be achieved using simple ketonesa sa ldehyde donors (Scheme 2). The driving force for this reactioni sm ost likely polymerization of the styrene by-product although al arge excesso ft he ketone is also used.…”
Section: Forward Shuttle Catalysis For the Functionalization Of Unsatmentioning
confidence: 99%